1988
DOI: 10.1128/aac.32.9.1450
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of PD 117,596 and reference antibiotics against 448 clinical bacterial strains

Abstract: The in vitro activity of PD 117,596, a new fluoroquinolone antibiotic, was tested against 448 bacterial isolates (15 genera) by agar dilution (inoculum, 104 CFU per spot). The activity of PD 117,596 was compared with that of 15 antibiotics against 327 gram-negative strains and with that of 8 other antibiotics against 121 gram-positive strains. PD 117,596 demonstrated the best activity against Klebsiella spp., Enterobacter spp., Acinetobacter spp., Serratia marcescens, and Branhamella catarrhalis (MICs for 90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…Inflammation and the achievement of a steady state in serum both appear to increase drug penetration into the vitreous humor (23). New investigational quinolones have excellent activity against the gram-positive pathogens (19,26,32,35) that are most commonly isolated in bacterial endophthalmitis (11,25,29). These observations, in conjunction with results of our pharmacokinetic studies, suggest that the fluoroquinolone antimicrobial agents may have a role in the prophylaxis and therapy of bacterial endophthalmitis.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Inflammation and the achievement of a steady state in serum both appear to increase drug penetration into the vitreous humor (23). New investigational quinolones have excellent activity against the gram-positive pathogens (19,26,32,35) that are most commonly isolated in bacterial endophthalmitis (11,25,29). These observations, in conjunction with results of our pharmacokinetic studies, suggest that the fluoroquinolone antimicrobial agents may have a role in the prophylaxis and therapy of bacterial endophthalmitis.…”
Section: Discussionsupporting
confidence: 74%
“…Pharmacokinetic data following direct injection into the vitreous body was described by a one-compartment model in which the rate of drug elimination followed first-order kinetics. Using composite pooled data, other investigators have also suggested that drug elimination from the vitreous body after direct administration follows first-order kinetics (8,35). The halflife of elimination for fleroxacin following direct injection was more rapid than that following systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…Members of this drug class possess a high degree of activity against aerobic gram-negative organisms but are generally less active against aerobic gram-positive cocci, particularly streptococci and enterococci (19). The recently developed quinolones tosufloxacin (1), sparfloxacin (12), CI-934 (2,8), PD 117596 (3,15), WIN 57273 (5), and PD 127391 (CI-960) (7,8,14,15,18), however, have good antimicrobial activity against these organisms. PD 127391 appears to be one of the most active of these agents.…”
mentioning
confidence: 99%
“…Proteus vulgaris (10) Providencia rettgeri (10) Providencia stuartii (10) (3,4,6,15,16). However, most clinically studied fluoroquinolones possess excellent potency against gram-negative organisms, especially members of the family Enterobacteriaceae, pathogenic Neisseria spp., H. influenzae, and B. catarrhalis (1,2,5,7,8,17).…”
mentioning
confidence: 99%
“…In addition, few of these compounds have exhibited a usable clinical potency for anaerobic organisms such as the Bacteroides spp. (3,4,15,16). The newer fluoroquinolones that do possess significant activity against gram-positive cocci and/or anaerobic bacteria generally contain a pyrrolidinyl or pyrrolyl group replacing the most commonly used 7-piperazinyl side chain (3,4,6,15,16).…”
mentioning
confidence: 99%